A Multitude of Latino Shakespeares [Review of Kliman, Bernice W. and Rick J. Santos (ed.). Latin American Shakespeares. Cranbury: Fairleigh Dickinson UP, 2005. 347 pp.] - Lola Aromovich (Ilha do Desterro)
The title of this volume of essays comes in handy: Latin American Shakespeares, in the plural, hinting at there being as many Shakespeares as there are productions, adaptations, translations, and films based on his work. Jorge Luis Borges himself affirmed, “When I think of Shakespeare I think of a multitude” (qtd in Tiffany 146). Nothing new here, since performance theory has made a point of not seeing the bard as one canonical, unified author, but as plural. The good news brought by this book is that it enables us to find out that so much has been written about Shakespeare in Latin America, especially in Brazil, Mexico and Argentina, while, alas, almost nothing appears from Paraguay or Bolivia. The editors, Bernice W. Kliman and Rick J. Santos, do not try to present hypotheses for this discrepancy, but the seventeen essays they select show a wide range of what has been studied in Brazil.